Operation 1027 - Naing, Myo. author. aut Link
XVII, 255 p. 1 illus.
Keywords: This book provides an in-depth examination of Operation 1027, in the dynamic landscape of Myanmar's protracted conflicts. This book examines the historical trajectory of the Three Brotherhood Alliance, shedding light on the interconnections and relationships that bind EAOs and other anti-junta forces to this operation. It also offers a timely exploration of the historical background and an intricate analysis of the events and factors surrounding Operation 1027. Myo Naing, prior to joining Shenzhen University as an associate research professor, served in three different think tanks in Myanmar, progressively as a lead researcher, senior research fellow, and technical advisor for over three years. Yizheng Zou, the corresponding author for this volume, is a professor of international relations at Shenzhen University. His publications on Southeast Asia and the Belt and Road Initiative include books and journal articles.